Nakasone Yasuhiro. - Hattori, Ryūji, 1968- ([S.l.])
1 online resource
Keywords: Yasuhiro Nakasone, who served as prime minister for more than five years in the 1980s, was one of Japan's leading postwar politicians. This book is a biography of him, but by interweaving international politics and media appraisals of him, it also serves as an examination of Japan's postwar politics. Nakasone was an innovative conservative who actively criticized the conservative mainstream, and this book reveals from both domestic and foreign policy perspectives how the Liberal Democratic Party governed. The Nakasone government served not only as the final phase of the Cold War era of LDP factional politics but also as the starting point for the general mainstream faction system that followed. With the lengthy passage of time since the end of the Cold War and the collapse of Japan's 1955 party system, there is a need to reassess Nakasone, showing that there was much more to him than the popular picture of him as a far-right hawk who loudly advocated for Japan to engage in autonomous self-defense and as an opportunist leader of a small faction, and to place the era in which Nakasone lived its proper historical context.